The Implementation of Principal’s Academic Supervision in SD Negeri 1 Beti Jaya - Efriyanti, Efriyanti (PPSDP International Journal of Education, 2025)
Academic supervision is one of the main tasks and responsibilities of the principal. This study aims to describe the implementation of supervision of the principal of a public elementary school according to the perception of teachers. The study was conducted in Kayu Agung sub-district, Ogan Komering Ilir district, South Sumatra Province by distributing questionnaires to teachers. The research questionnaire used has been validated using the expert judgment technique. Data from the questionnaire were processed quantitatively using the percentage technique. The results of the study showed that the principal of SD Negeri 1 Beti Jaya studied had carried out academic supervision tasks. Of all the tasks, the task of motivating teachers to utilize information technology in learning in each subject is the task with the highest implementation. Conversely, the task with the lowest implementation is understanding the concepts, principles, theories/technologies, characteristics, and development trends of the learning/guidance process for each subject and is in the fourth indicator, namely planning supervision activities with teachers. Thus, the implementation of academic supervision of the principal at SD Negeri 1 Beti Jaya still needs to be improved.